2020
DOI: 10.1021/acs.inorgchem.0c00955
|View full text |Cite
|
Sign up to set email alerts
|

Half-Sandwich Ruthenium Complexes for One-Pot Synthesis of Quinolines and Tetrahydroquinolines: Diverse Catalytic Activity in the Coupled Cyclization and Hydrogenation Process

Abstract: Four types of half-sandwich ruthenium complexes with an N,O-coordinate mode based on hydroxyindanone-imine ligands have been prepared in good yields. These stable ruthenium complexes exhibited high activity in the catalytic synthesis of quinolines from the reactions of amino alcohols with different types of ketones or secondary alcohols under very mild conditions. Moreover, the methodology for the direct one-pot synthesis of tetrahydroquinoline derivatives from amino alcohols and ketones has been also develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
(50 reference statements)
2
18
0
Order By: Relevance
“…The ruthenium complex crystallized in the monoclinic space group P 2 1 c (Figure ). Geometric data are listed in the Supporting Information (Table S1), and the characteristic bond lengths and angles which are consistent with the reported values are summarized in the footnote of Figure . The ruthenium center of this complex displayed a typical three-legged piano-stool conformation.…”
Section: Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The ruthenium complex crystallized in the monoclinic space group P 2 1 c (Figure ). Geometric data are listed in the Supporting Information (Table S1), and the characteristic bond lengths and angles which are consistent with the reported values are summarized in the footnote of Figure . The ruthenium center of this complex displayed a typical three-legged piano-stool conformation.…”
Section: Results and Discussionsupporting
confidence: 72%
“…The half-sandwich moiety has emerged as a important building block in organometallic complexes synthesis and catalysis due to their high stability, good solubility, easy modification, and excellent catalytic activity. The detailed advantages of the half-sandwich moiety are as follows: (i) the dichloro-bridged metal precursor can be easily prepared in good yields through inorganic metal salts; (ii) the metal center was protected by the half-sandwich structure which avoided the side reactions; (iii) the electron and steric effects can be tuned conveniently by choosing different substituents. Among these types of complexes, half-sandwich Ru­(II) complexes were frequently employed as the building blocks in the preparation of diverse compounds which showed particular activity in catalysis, coordination-driven self-assembly, and biochemistry. Recent study indicated that the half-sandwich Ru­(II) complexes with nitrogen-containing ligands showed good catalytic efficiency in diverse organic reactions. , However, there are limited studies of RA reactions using half-sandwich Ru­(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Another approach to synthesize 1,2,3,4-tetrahydroquinolines 2 was pursued with the N,O-chelate half-sandwich ruthenium complex Ru-5 starting from 2-aminobenzyl alcohols and ketones. [25] The cyclization to form the corresponding quinoline and its hydrogenation were combined in a one-pot synthesis. Thus, usage of hydrogen pressure, low catalyst loading (0.1 mol%) and a stoichiometric amount of base produced the desired 1,2,3,4-tetrahydroquinolines 2 in good yields.…”
Section: 234-tetrahydroquinolines and 1234-tetrahydronaphthyridinesmentioning
confidence: 99%
“…Yao and coworkers reported the synthesis of quinoline derivatives starting from amino alcohols and ketones as well as secondary alcohols catalyzed by half-sandwich N,O-chelate ruthenium complexes. 14 Yang's group reported the synthesis of quinolines via acceptorless dehydrogenative coupling of o-aminobenzyl alcohols with ketones in the presence of carbonate salt with the 2,2′-bibenzimidazole ligand [( p-cymene)Ru(BiBzImH 2 )Cl][Cl]. 15 The reaction doesn't require the addition of strong inorganic bases to carry out acceptor-free dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%